THE EXPANDING CLINICAL SPECTRUM OF CHOROIDAL EXCAVATION IN MACULAR DYSTROPHIES. Issue 10 (October 2018) - Battaglia Parodi, Maurizio; Casalino, Giuseppe; Iacono, Pierluigi; Introini, Ugo; Adamyan, Tatevik; Bandello, Francesco
Abstract : Purpose: To assess the prevalence and the clinical course of focal choroidal excavation (FCE) in patients affected by macular dystrophies. Methods: Prospective case series. All the patients underwent a complete ophthalmologic examination, including best-corrected visual acuity and spectral domain optical coherence tomography. The presence of choroidal neovascularization (CNV) was assessed on the basis of the leakage detected on fluorescein angiography. Results: A total of 162 eyes from 81 patients with macular dystrophy were included in the study. FCE was diagnosed in seven eyes (4.3% of the eyes), including four eyes with Best vitelliform dystrophy, two eyes with pattern dystrophy associated with pseudoxanthoma elasticum, and one case of Stargardt disease. In eyes with FCE and macular dystrophy, the mean best-corrected visual acuity was 0.4 ± 0.1 logarithm of the minimum angle of resolution (approximately corresponding to 20/50 Snellen equivalent) at baseline and was stable to 0.41 ± 0.1 logarithm of the minimum angle of resolution (approximately corresponding to 20/50 Snellen equivalent) at the final visit. In four of these seven eyes, FCE was associated with a subfoveal CNV. The CNV was managed with one intravitreal anti–vascular endothelial growth factor injection, achieving the complete anatomical stabilization of the CNV and recovery of the best-corrected visual acuity. Conclusion: Focal choroidal excavation can be infrequently encountered in patients with macular dystrophies. The presence of CNV may complicate FCE in these patients, and anti–vascular endothelial growth factor seems to be an effective treatment with no progression of FCE over time. Abstract : In eyes with macular dystrophy, occurrence of a focal choroidal excavation is an infrequent but possible finding. In these eyes, the occurrence of a choroidal neovascularization was successfully treated with one single anti–vascular endothelial growth factor injection with no progression of the focal choroidal excavation.